Islam Berkemadjoean Perspektif Globalisasi: Kontribusi Islam Indonesia pada Peradaban Global - Teguh Luhuringbudi; Fitri Liza; Novian Akbar (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
This research is aimed at studying the role of the Muhammadiyah Association in global relationships based on slogan, watchwords, plans, and Islamic activities. This study uses a communication and media approach as an effort to discuss a Muhammadiyah organization in the era of globalization. The perspective used in this study is the perspective of